Method for treating coated cutting tools

By setting appropriate laser impact enhancement energy density on cemented carbide cutting tools and using black paint or absorption layers, combined with surface treatment such as sandblasting, the problem of poor laser impact enhancement effect in the existing technology has been solved, which has significantly improved the The cutting tool's edge toughness and wear resistance extend the tool life.

CN114222643BActive Publication Date: 2024-12-31SANDVIK COROMANT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080057203.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2020-08-27
Publication Date
2024-12-31
Estimated Expiration
2040-08-27

AI Technical Summary

Technical Problem

In the prior art, when laser impact strengthening treatment of cemented carbide cutting tools, the energy density is too low and the toughness and wear resistance cannot be improved. If the energy density is too high, the anti-cracking resistance of the blade line may be reduced, and the commonly used surface treatment methods cannot be effective. Improve the performance of cutting tools.

Method used

Using laser impact enhancement (LSP) treatment coating cutting tool, set the LSP energy density within 0.4J/mm2 to 1.6J/mm2, combine black paint or absorbent layer to replace the paint, apply laser pulses to increase residual stress, and After LSP, sandblasting, polishing or brushing are performed to improve surface roughness and stress levels.

Benefits of technology

It significantly improves the edge toughness and wear resistance of cutting tools, extends the tool life, and avoids the problem of surface stress reduction caused by the excessive energy density of LSP, and improves cutting performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114222643B_ABST
    Figure CN114222643B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for treating a coated cutting tool using laser shock peening (LSP), wherein the coated cutting tool consists of a substrate and a coating, wherein the substrate is cemented carbide or cermet, preferably cemented carbide, and wherein the coating comprises a CVD layer and / or a PVD layer. The method comprises the step of applying LSP to at least a portion of the cutting tool, wherein the LSP energy density is 0.4 J / mm 2 Up to 1.6J / mm 2 within, and wherein the LSP comprises applying laser pulses to at least a portion of the cutting tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the laser shock peening treatment of coated cutting tools, wherein the cutting tools have a substrate of cermet or cemented carbide and a coating comprising a layer produced by CVD and / or PVD. Background Art

[0002] Cermets and cemented carbides are materials consisting of hard components in a metal binder. These materials are common substrates in cutting tools and have properties such as high hardness, high wear resistance, and high toughness. These substrates are usually coated with wear-resistant coatings, such as CVD coatings such as TiCN and aluminum oxide layers or PVD coatings such as TiN and TiAlN layers.

[0003] The coated cutting tools are usually surface treated to further improve their cutting life. Common surface treatment methods are brushing to smooth the outer surface or shape the cutting edge, shot blasting to smooth the surface, and to affect the residual stress level in the cemented carbide surface area or coating.

[0004] Laser shock peening is a method that uses lasers to influence the properties of a surface area. Laser pulses of short duration and high intensity are scanned over the surface. Each laser pulse generates a local plasma that forms on the surface, thereby generating a shock wave that propagates into the object being processed. The shock wave affects the material of the surface area, increasing hardness, toughness, and changing the residual stress level.

[0005] WO 2018 / 215996 A1 discloses a method for treating cemented carbide cutting tools by laser shock peening. Summary of the invention

[0006] It is an object of the present invention to provide an improved method for treating coated cutting tools comprising a substrate of cermet or cemented carbide.

[0007] At least one of these objects is achieved with the method according to clause 1. Preferred embodiments are listed in the dependent clauses.

[0008] The present invention relates to a method for treating a coated cutting tool using laser shock peening (LSP), wherein the coated cutting tool consists of a substrate and a coating, wherein the substrate is cemented carbide or cermet, preferably cemented carbide, and wherein the coating comprises a CVD layer and / or a PVD layer, wherein the method comprises the step of applying LSP to at least a portion of the cutting tool, wherein the LSP energy density is between 0.4 J / mm 2 Up to 1.6J / mm 2 Within, preferably within 0.9J / mm2 Up to 1.4J / mm 2 More preferably within 1.1 J / mm 2 Up to 1.3J / mm 2 Inside.

[0009] Surprisingly, it was found that if the LSP energy density was set at 0.4 J / mm 2 Up to 1.6J / mm 2 Within (preferably 0.9J / mm 2 Up to 1.4J / mm 2 If the LSP energy density is too low, the LSP impact force is too low to achieve improved edge line toughness or wear resistance. If the LSP energy density is too high, there is a higher risk of reduced stress in the surface area, resulting in reduced edge line chipping resistance.

[0010] In one embodiment of the present invention, the LSP comprises applying laser pulses to the at least a portion of the cutting tool, and wherein the laser pulse energy density is 0.04 J / mm 2 Up to 1.0J / mm 2 , preferably 0.04J / mm 2 -0.5J / mm 2 , more preferably 0.04 J / mm 2 -0.1J / mm 2 , even more preferably 0.05 J / mm 2 -0.07J / mm 2 .

[0011] In one embodiment of the invention, black paint or black tape is applied to the coated cutting tool prior to applying the LSP. One advantage of using black paint or black tape is that the underlying coating can be maintained without any reduction in thickness or change in appearance.

[0012] In one embodiment of the invention, the coating comprises an outer layer of one or more of TiN, TiCN, TiC, TiB2, ZrCN, TiAlN or TiSiN. These layers can be used as an absorbing layer, replacing paint or tape. The advantage of these layers is that they can be deposited as part of a CVD or PVD coating, thereby avoiding the additional step of applying black tape or paint. Another advantage is that the use of these layers makes the effect of LSP appear more pronounced, thereby inducing higher levels of residual stress in the surface area of ​​the substrate.

[0013] In one embodiment of the present invention, the thickness of the outer layer is preferably 2 μm-5 μm. If the thickness of the outer layer is too thin, the thickness of the wear-resistant layer below will be reduced during the LSP. If the thickness is greater than 5 μm, the residual stress induced in the substrate is small, so the improvement of the tool life by the LSP is not obvious.

[0014] In one embodiment of the present invention, the coated cutting tool further comprises an Al2O3 layer between the substrate and the outer layer. The Al2O3 layer is preferably an α-Al2O3 layer. This is advantageous because it is a very wear-resistant layer.

[0015] In one embodiment of the present invention, the coated cutting tool further comprises a TiCN layer located between the substrate and the outer layer.

[0016] In one embodiment of the present invention, the coated cutting tool further comprises a TiAlN layer located between the substrate and the outer layer.

[0017] In one embodiment of the present invention, the total thickness of the coating is 2 μm-20 μm.

[0018] In one embodiment of the present invention, the total thickness of the coating is 2 μm-10 μm.

[0019] In one embodiment of the present invention, the cutting tool comprises a rake face and a flank face and a cutting edge therebetween, and wherein the LSP is applied to a portion of the cutting edge and at least a portion of the rake face.

[0020] In one embodiment of the invention, a sandblasting, polishing and / or brushing step is performed after the LSP step, preferably a sandblasting step, such as shot peening. The advantages of sandblasting, polishing and brushing are that the surface of the cutting tool can be finished by any of these techniques, so that the cutting performance of the cutting tool can be improved. Shot peening is advantageous because both the surface roughness and the residual stress level in the coating can be influenced, and lower surface roughness and reduced tensile stress levels or higher compressive stress levels can be achieved in the coating, so that the cutting tool life can be extended.

[0021] In one embodiment of the invention, the cutting tool comprises a rake face and a flank face and a cutting edge therebetween, and wherein the LSP is applied only to a portion of the cutting edge of the cutting tool and a portion of the rake face and / or flank face, wherein the width (b) of the region is at most 5 mm from the cutting edge, preferably, the width (b) of the region is 1 mm-5 mm from the cutting edge. It is advantageous to apply the LSP at least to the region involved in cutting. In the application, the extension from the edge on the rake face should be at least the cutting depth a p .

[0022] In one embodiment of the present invention, the LSP is applied along the entire cutting edge of the cutting tool.

[0023] In one embodiment of the present invention, the LSP is applied to the entire rake face of the cutting tool.

[0024] In one embodiment of the present invention, the LSP is applied to the entire rake face, the entire edge and the entire flank face of the cutting tool.

[0025] In one embodiment of the present invention, the wavelength of the laser during the LSP step is within the range of 1000 nm to 1100 nm, preferably within the range of 1050 nm to 1070 nm, more preferably about 1064 nm.

[0026] In one embodiment of the invention, the frequency of the laser during the LSP step is within the range of 150 000 Hz to 250 000 Hz, preferably about 200 000 Hz.

[0027] In one embodiment of the present invention, the pulse duration of the laser during the LSP step is within 0.005 ns to 0.02 ns, preferably about 0.01 ns to 0.02 ns.

[0028] In one embodiment of the invention, the average effect of the laser during the LSP step is within 13W to 16W, preferably about 15W.

[0029] In one embodiment of the present invention, the spot size of the laser during the LSP step is within 0.03 mm to 0.05 mm, preferably about 0.04 mm.

[0030] In one embodiment of the present invention, the peak power density of the laser during the LSP step is 3 GW / mm 2 Up to 7GW / mm 2 Within, preferably about 6GW / mm 2 The peak power density level can be varied by changing the frequency, pulse length, laser effect or spot size. Peak power density is 3GW / mm 2 Up to 7GW / mm 2 This is advantageous because the peak pressure generated is high, thereby improving the service life of the cutting tool.

[0031] In one embodiment of the present invention, the LSP is applied to the coated cutting tool while the coated cutting tool is immersed in water.

[0032] Other objects and features of the present invention will become apparent from the following embodiments considered in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a diagram of a cutting tool (1) that can be treated according to the invention, wherein the rake face (2), the flank face (4) and the cutting edge (3) are indicated. The geometry of the cutting tool corresponds to the geometry used in the following examples.

[0034] Figure 2 is a schematic diagram of the location and extension of the LSP region according to one embodiment of the present invention, showing the rake face (2) and the cutting edge (3) of the cutting tool (1).

[0035] Figure 3 Schematic diagram of a laser pulse (circle) scanned over an area with a pulse step size x. The pulses overlap each other so that the entire area or a portion is treated with LSP.

[0036] definition

[0037] "Cutting tool" in this context refers to a cutting tool used in metal cutting applications, such as an insert, end mill or drill. For example, the application area may be turning, milling or drilling.

[0038] The term "cemented carbide" herein refers to a material comprising at least 50 wt. % WC, other possible hard components commonly used in the art of manufacturing cemented carbide, and preferably one or more metal binder phases selected from Fe, Co and Ni.

[0039] "Cermet" herein refers to a material comprising a hard component and a metal binder phase, wherein the hard component is one or more of titanium carbonitride, titanium carbide and titanium nitride. The metal binder phase in the cermet is preferably selected from one or more of Fe, Co and Ni, preferably Co. Other common hard components in the field of cermets are selected from carbides, nitrides or carbonitrides of Ti, Ta, Nb, Zr, V and Cr. The cermet material does not contain free hexagonal WC. Titanium carbonitride-based cermet materials are the most common cermet materials today.

[0040] "LSP energy density" herein refers to the average energy density applied to the LSP treated portion or region of the cutting tool. An increase in pulse overlap or an increase in laser pulse energy density results in an increase in LSP energy density.

[0041] The "laser pulse energy density" in this article refers to the average energy density of a single laser pulse. An increase in pulse duration or an increase in effect leads to an increase in laser pulse energy density.

[0042] "Shot peening" herein refers to a process using abrasive particles in which material is removed from the treated surface, usually by abrasive wear. Shot peening is well known in the cutting tool art and is, for example, known to introduce residual stresses in the coatings of cutting tools. Example

[0043] Exemplary embodiments of the present invention will now be disclosed in more detail and compared with comparative embodiments.Coated cutting tools (inserts) were prepared, analyzed and evaluated in cutting tests.

[0044] Substrate

[0045] ISO R390-11T308M-PM type cemented carbide substrate for milling was manufactured. Figure 1 .

[0046] Two different cemented carbide compositions were made. Substrate A was made from a powder mixture consisting of about 13.50 wt % Co, 0.57 wt % Cr, and the balance WC. Substrate B was made from a powder mixture consisting of about 9.14 wt % Co, 1.15 wt % Ta, 0.27 wt % Nb, 0.05 wt % Ti, and the balance WC. The powder mixture was ground, dried, pressed into a green compact, and sintered at 1450° C. to form a sintered cemented carbide substrate.

[0047] coating

[0048] A CVD coating was deposited on the two cemented carbide compositions. The CVD coating consisted of an inner TiN layer with a thickness of 0.5 μm, a subsequent wear-resistant TiCN layer with a thickness of 3.5 μm and a wear-resistant α-Al2O3 layer with a thickness of 3 μm thereon. Thereafter, an outer TiN layer with a thickness of 2 μm was deposited. The total thickness of the coating was about 9 μm.

[0049] LSP process

[0050] The LSP is applied to the rake face area of ​​the coated cutting tool and also covers the edge. The width b of the area measured perpendicular to the cutting edge of the cutting tool is about 3 mm. The extension a along the main cutting edge is about 6 mm and the extension c along the auxiliary cutting edge is about 3 mm. See Figure 2 Schematic diagram of the LSP region.

[0051] The LSP process was applied using 6 mm of water on the surface. During the LSP process, the cutting tool was immersed in water.

[0052] The laser settings during LSP are as follows:

[0053] Wavelength: 1064nm

[0054] Frequency: 200kHz

[0055] Pulse duration: 0.01ns

[0056] Pulse diameter, d: 0.04mm

[0057] Laser power: 14.8W

[0058] Peak power density: 5.89GW / mm 2

[0059] The laser pulse energy density is 0.059 J / mm 2 , calculated as follows:

[0060]

[0061]

[0062]

[0063] The LSP energy density is adjusted by changing the pulse distance (i.e., pulse step length x) to change the pulse overlap, making the pulse distance smaller, so that a larger pulse overlap leads to a larger LSP energy density. The laser pulse overlap is related to the pulse step length x and the pulse diameter d:

[0064]

[0065] The LSP energy densities of the samples are shown in Table 1.

[0066]

[0067]

[0068] Table 1

[0069]

[0070]

[0071] Shot peening process

[0072] After the LSP, the cutting tool was shot peened to remove the outer TiN layer. The shot peening time was slightly adjusted to remove all TiN from the LSP treated rake face area. The shot peening was performed using abrasive aluminum oxide and a gas pressure of 2.1 bar. Samples A0 and B0 were also shot peened.

[0073] Cutting performance 1

[0074] The inserts with substrate A were then tested in a milling operation under the following parameters:

[0075] Workpiece materials: Unhardened Dievar, PL 129 200x200x100, MC P3.0.Z.AN, CMC 03.11,

[0076] Load: M10205

[0077] v c =200m / min

[0078] f z =0.15mm

[0079] a e =12mm

[0080] a p =3.0

[0081] z=1

[0082] Cutting length = 12mm

[0083] No cutting fluid was used.

[0084] Blade model R390-11T308M-PM

[0085] The tool life criterion was set at a chipping of at least 0.5 mm at the edge line. Tool life was expressed as the average number of cuts required to achieve this criterion. The average tool life is shown in Table 2, which is the average number of cuts and is the average of 8 parallel cutting tests.

[0086] Table 2

[0087]

[0088] Cutting performance 2

[0089] The inserts with substrate B were then tested in a milling operation under the following parameters:

[0090] Workpiece materials: Unhardened Dievar, PL 129 200x200x100, MC P3.0.Z.AN, CMC 03.11,

[0091] Load: M10205

[0092] v c =160m / min

[0093] f z =0.2mm

[0094] ae =12mm

[0095] a p =3.0

[0096] z=1

[0097] Cutting length = 12mm

[0098] No cutting fluid was used.

[0099] Blade model R390-11T308M-PM

[0100] The tool life criterion is set as a notch of at least 0.5 mm in the edge line. Tool life is expressed as the average number of cuts required to achieve this criterion. The average tool life is shown in Table 3, which is the average number of cuts and is the average of 8 parallel cutting tests.

[0101] Table 3

[0102]

[0103] Although the present invention has been described in conjunction with various exemplary embodiments, it should be understood that the present invention is not limited to the disclosed exemplary embodiments, but rather, the present invention is intended to cover various modifications and equivalent arrangements in the appended claims. In addition, it should be recognized that any disclosed form or embodiment of the present invention may be incorporated into any other disclosed, described or suggested form or embodiment as a general matter of design choice. Therefore, it is intended to be limited only as indicated by the scope of the claims appended hereto.

Claims

1. A method for treating a coated cutting tool (1) using laser shock peening, wherein the coated cutting tool consists of a substrate and a coating, wherein the total thickness of the coating is 2 μm-20 μm, wherein the substrate is a cemented carbide or a metal ceramic, and wherein the coating comprises a CVD layer and / or a PVD layer, wherein the method comprises the step of applying laser shock peening to at least a portion of the cutting tool (1), wherein the laser shock peening energy density is 0.4 J / mm 2 Up to 1.6J / mm 2 Inside.

2. The method of claim 1 , wherein the laser shock peening comprises applying laser pulses to the at least a portion of the cutting tool, and wherein the laser pulse energy density is 0.04 J / mm 2 Up to 1.0J / mm 2 .

3. The method according to claim 1 or 2, wherein the wavelength of the laser during the laser shock peening step is within 1000 nm to 1100 nm.

4. The method according to claim 1 or 2, wherein black paint or black tape is applied to the coated cutting tool (1) before applying the laser shock peening.

5. The method according to claim 1 or 2, wherein the coating comprises an outer layer of one or more of TiN, TiCN, TiC, TiB2, ZrCN, TiAlN or TiSiN, and the thickness of the outer layer is 2 μm-20 μm.

6. The method according to claim 5, wherein the coated cutting tool (1) further comprises an Al2O3 layer located between the substrate and the outer layer.

7. The method according to claim 5, wherein the coated cutting tool (1) further comprises a TiCN layer located between the substrate and the outer layer.

8. The method according to claim 5, wherein the coated cutting tool (1) further comprises a TiAlN layer between the substrate and the outer layer.

9. The method according to claim 1 or 2, wherein the cutting tool (1) comprises a front cutting face (2) and a rear cutting face and a cutting edge (3) therebetween, wherein the laser shock peening is applied to a portion of the cutting edge (3) and at least a portion of the front cutting face (2).

10. The method according to claim 1 or 2, wherein the laser shock peening step is followed by a sandblasting, polishing and / or brushing step.

11. The method according to claim 1 or 2, wherein the cutting tool (1) comprises a rake face (2) and a flank face and a cutting edge (3) therebetween, and wherein the laser shock peening is applied only to a portion of the cutting edge (3) and a portion of the rake face (2) and / or flank face (4) of the cutting tool (1), wherein: The width (b) of the laser shock peened area is at most 5 mm from the cutting edge (3).

12. The method according to claim 1 or 2, wherein the frequency of the laser during the laser shock peening step is within the range of 150 000 Hz to 250 000 Hz.

13. The method of claim 1 or 2, wherein the average power of the laser during the laser shock peening step is within 13W to 16W.

14. The method according to claim 1 or 2, wherein the peak power density of the laser during the laser shock peening step is 3 GW / mm 2 Up to 7GW / mm 2 Inside.

15. The method according to claim 1 or 2, wherein the laser shock peening energy density is 0.9 J / mm 2 Up to 1.4J / mm 2 Inside.